2017
DOI: 10.21037/jovs.2017.03.09
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic techniques and strategies for gastrointestinal GISTs

Abstract: The laparoscopic approach is widely accepted surgical treatment for gastrointestinal submucosal tumors (SMTs). In this chapter, we will introduce laparoscopic techniques and strategy for gastrointestinal SMTs, in accordance with those for gastrointestinal stromal tumors (GISTs). The indication for a laparoscopic approach has been related to tumor size. The upper limit of tumor size has increased, according to recent trends, and there is no established guideline for a lower limit. All patients undergoing laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In our study, among 20 patients underwent subtotal gastrectomies, 8 had concurrent gastric intraepithelial neoplasia, 5 had another submucosal tumor lesion discovered at the operative procedure, and 7 had tumors at difficult regions, such as cardia and pylorus. Many studies showed different surgical techniques are required depending on the tumor location and configuration to ensure a complete resection with a negative resection margin 26-29.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, among 20 patients underwent subtotal gastrectomies, 8 had concurrent gastric intraepithelial neoplasia, 5 had another submucosal tumor lesion discovered at the operative procedure, and 7 had tumors at difficult regions, such as cardia and pylorus. Many studies showed different surgical techniques are required depending on the tumor location and configuration to ensure a complete resection with a negative resection margin 26-29.…”
Section: Methodsmentioning
confidence: 99%
“… 1 Postoperative stenosis of the gastric lumen is a described adverse event after laparoscopic wedge resection of submucosal tumors located on the lesser curvature. 2 , 3 We describe a case of EUS-guided gastroenterostomy facilitated by extrinsic abdominal compression to treat gastric obstruction resulting from a laparoscopic wedge resection of a gastrointestinal stromal tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The limitation of tumor size for laparoscopic surgery has traditionally been considered “diameter not more than 2 cm” but recent published data show the safety and feasibility of laparoscopic resection in large (>5 cm) and giant (>10 cm) gastric GISTs. This limit should increase in the near future and current guidelines do not state an absolute indication regarding tumor size [ 12 ]. Open surgery still plays a fundamental role in GISTs that require complex multivisceral resection, large lesions necessitating delicate tissue handling (to prevent tumor rupture or spill-age), or large abdominal incisions for specimen retrieval [ 9 ].…”
Section: Discussionmentioning
confidence: 99%